2019
DOI: 10.1167/19.5.7
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of a perceptual decision

Abstract: Previous research suggests that cognitive factors acting in a top-down manner influence the perceptual interpretation of ambiguous stimuli. To examine the temporal unfolding of these influences as a perceptual decision evolves, we have implemented a modified version of the stream-bounce display. Our novel approach allows us to track responses to stream-bounce stimuli dynamically over the entire course of the motion sequence rather than collecting a subjective report after the fact. Using a trackpad, we had par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Fooken and Spering (2019) used a go/no-go manual interception paradigm to show that predictive eye and hand movements jointly signal the upcoming decision about a future target. Similar predictive behavioral responses are shown in a manual tracking task, where different cursor speeds were related to different perceptual decisions (Zeljko et al, 2019). Mann et al (in press) used a virtual tennis environment to show how a combination of tracking and predictive eye and head movements helps keep gaze close to the ball despite the ball bouncing as it approaches.…”
Section: Combining Predictions Of Eye Arm and Object Movementsmentioning
confidence: 76%
“…Fooken and Spering (2019) used a go/no-go manual interception paradigm to show that predictive eye and hand movements jointly signal the upcoming decision about a future target. Similar predictive behavioral responses are shown in a manual tracking task, where different cursor speeds were related to different perceptual decisions (Zeljko et al, 2019). Mann et al (in press) used a virtual tennis environment to show how a combination of tracking and predictive eye and head movements helps keep gaze close to the ball despite the ball bouncing as it approaches.…”
Section: Combining Predictions Of Eye Arm and Object Movementsmentioning
confidence: 76%
“…All participants reported normal hearing and normal or corrected to normal vision, all were naïve as to the purpose of the experiment, and all reported being unfamiliar with the stream-bounce stimulus. We have selected a sample size of 25 participants per experimental group throughout this study based on a conservative approach to previous findings that stream-bounce effects are typically large ( d > .8), but serial dependency effects and temporal context effects are typically medium (e.g., Zeljko et al, 2019, found a medium effect size of d = .56 for serial dependency in a modified stream-bounce design; Parise & Ernst, 2017, found a medium effect size of φ ∼ .3 for serial dependence of response in a stream-bounce task; and Intaitė et al, 2013, found a medium effect size of d ∼ .5 for temporal context effects on Necker cube perception). We conducted a sensitivity analysis using G*Power to validate this assumption and found that two-tailed dependent means t -tests with 25 participants and an alpha of .05 could detect a medium effect size of .59 with 80% power (Faul et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Sensory input provides the brain with information that reflects the current state of the world, and prior knowledge, gained through experience, provides the brain with information about how the world works (e.g., Gekas et al, 2015 ; Gilbert & Sigman, 2007 ; Kersten et al, 2004 ; Kornmeier et al, 2009 ; Maloney et al, 2005 ; Summerfield & Egner, 2009 ; Wang et al, 2013 ). While the sensory input reflects the state of the world, it always underspecifies it; sensory information is varyingly noisy, incomplete, and weak, and so in general, it is ambiguous (Parise & Ernst, 2018 ; Urgen & Boyaci, 2021 ; Zeljko et al, 2019 ). However, perceptual decisions are reached without the impression of ambiguity as the incoming sensory information is interpreted within a framework of prior knowledge (e.g., Ernst & Bülthoff, 2004 ; Gilbert & Sigman, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Next, Zeljko et al ( 2019 ) implemented a modified version of the stream-bounce display that tracked responses to stream-bounce stimuli dynamically over the entire course of the motion sequence rather than collecting a subjective report after the fact. Participants used a trackpad to control a cursor to track a stream-bounce target actively from the beginning to the end of its trajectory.…”
Section: Introductionmentioning
confidence: 99%